How 30 great ads were made from idea to campaign - Williams, Eliza (United Kingdom Laurence King Publishing Ltd, 2012)
This book takes readers behind the scenes in the world of advertising. It looks at key advertising campaigns from the last ten years, examining how they were developed. Technical information on how the ads were created is accompanied by anecdotes from the creatives, directors and clients, with accounts of how the ads were made and the problems encountered along the way.

Each campaign is illustrated with imagery showing the stages it went through in development--including sketches and early ideas that may have been abandoned, storybooks, animatics and photos from shoots, and shots of the final ads.

As well as offering an insight into the working practices within advertising, this book also demonstrates how the industry is currently experiencing a period of rapid change, and shows the different skills that are now required to work in advertising.
Donated by Prof. Michelle Roxas
Keywords: Advertising; Advertising -- Case studies; Advertising -- Hsitory -- 21st century; Advertising campaigns